COVID-19 and the malaria elimination agenda in Africa: Re-shifting the focus. Issue 12 (2nd December 2022) - Patrick, Sean M.; Cox, Sarah N.; Guidera, Kathryn E.; Simon, Molly J.; Kruger, Taneshka; Bornman, Riana
ABSTRACT: The global Coronavirus disease 2019 (COVID-19) pandemic has resulted in public health, political, scientific and private sector response at an unprecedented scale. However, this shift in focus has caused widespread disruption to global health services and has the potential to reverse gains made in efforts to control malaria. If health systems are not able to maintain malaria control interventions while managing the response to the COVID-19 pandemic, malaria cases will increase, thereby placing even more strain on already overtaxed systems. Using a Narrative Review Approach, this commentary explores the impact of COVID-19 on progress made with malaria control and prevention strategies in Africa; and discusses possible mitigation steps to aid community resilience building, through proactive planning and implementation of integrated, inclusive and sustainable strategies to re-shift the focus to attain the malaria elimination goals. We propose strengthening community partnerships, where academia and communities should collaborate and these knowledge-sharing strategies be implemented in order for awareness and interventions to become more networked, inclusive, resilient and effective. Communities should be viewed as 'thought partners', who challenge conventional strategies and aid in developing innovative approaches to community resilience building.